Analysis of Online Accessibility of Public Access Catalogue on Slims and Inlislite Applications Based on WCAG 2.0 - Cahyono, M. Annas Dwi; Inawati, Inawati (Universitas Pendidikan Indonesia, 2022)
This study aims to determine the accessibility level of OPAC in the SLiMS and INLISLite applications. Four main guidelines on aspects of website accessibility will be analyzed: perceivable, operable, adaptable, and robust. The four guidelines are based on the Web Content Accessibility Guidelines (WCAG). This study uses a quantitative approach with descriptive methods and data analysis techniques using manual checks based on the WCAG-EM guidelines focusing on two levels, A and AA. The results of the research based on four indicators are (1) perceivable in SLiMS and INLISLite experiencing problems in providing alternative texts, (2) operable in SLiMS and INLISLite found problems with focus elements, (3) understandable in SLiMS and INLISLite failing to meet the criteria for providing language, and (4) robust, both applications have succeeded in utilizing HTML syntax according to the provisions. So, of the four indicators, the SLiMS and INLISLite applications still need to meet several criteria at level A, namely the criteria for using language, using colour, and providing alternative text on non-text elements. Meanwhile, at the AA level, there is a failure in the focus element.